Impacts of Oceanic Preexisting Conditions on Predictions of Typhoon Hai-Tang in 2005 - Akiyoshi Wada; Norihisa Usui (Advances in Meteorology)
We investigated the impact of variations in oceanic preexisting conditions on predictions of Typhoon Hai-Tang (2005) by using a coupled atmosphere-ocean model with 6-km horizontal resolution and providing the oceanic initial conditions on 12 July from 1997 to 2005 to the model. Variations in oceanic preexisting conditions caused variation in predicted central pressure of nearly 18 hPa at 72 h, whereas sea-surface cooling (SSC) induced by Hai-Tang caused a predicted central pressure difference of about 40 hPa. Warm-core oceanic eddies up to a few hundred kilometers across and a deep mixed layer climatologically distributed in the western North Pacific led to high mixed-layer heat potential, which increased latent heat flux, water vapor, and liquid water contents around Hai-Tang's center. These increases were closely associated with Hai-Tang's intensification. SSC negatively affected the eyewall, whereas variations in oceanic preexisting conditions remarkably affected spiral rainbands and the magnitude of SSC.